Factors that influence customer satisfaction among compact SUVs car owners: a case study on an automotive company in Malaysia - Hanifah Binti Moksin; Mohamad Irwan Bin Khalil; Shahrizal Bin Md Zainal; Low Chee Him; Yap Den Hau; Musalizam Bin Musa (Asian Journal of Social Science Research, 2023)
This study aimed to examine the relationship between comfort, cabin space, design, social life, value for money, and customer satisfaction among compact SUV car owners at a Malaysian automaker. The study involved 407 samples of compact SUV car owners who responded to a questionnaire with their opinions. The findings revealed that comfort, cabin space, and value for money were significant factors in determining customer satisfaction among owners of compact SUVs. Despite the subjectivity of design, this factor did not significantly influence the overall customer satisfaction of compact SUV car owners. Similarly, social life factors, such as the social status associated with owning a particular car brand or model, were discovered to have no significant impact on customer satisfaction. The study highlights the need for this automaker to prioritize comfort, cabin space, and value when designing and marketing compact SUVs to increase customer satisfaction. Future research will examine strategies to optimize the comfort, cabin space, and value for money aspects to meet customer expectations and increase their overall satisfaction.